1996
DOI: 10.11646/bde.12.1.15
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Bryophytes from the Cape Verde Islands</strong></p>

Abstract: Almost 450 specimens of bryophytes, so far the largest collection of bryophytes ever made on the Cape Verde Islands, were collected in 1995 by the second author on the major islands of the archipelago. In addition to the so far unpublished results of recent collections, a complete survey of the bryophyte flora of the Cape Verde Islands is given. A hundred and sixty two species (2 species of hornworts, 36 species of hepatics and 124 species of mosses) are so far known from this archipelago.124

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…In most of the previous studies, species richness of bryophytes was found to be independent of the degree of isolation of both true islands (Menzel & Passow-Schindhelm, 1990;Dirkse, Bouman & Losada-Lima, 1993;Frahm et al, 1996) and habitat islands (Kimmerer & Driscoll, 2000). The lack of relationship between bryophyte species richness and habitat isolation was confirmed for cliffs in our study (it was not analysed for talus slopes, which are rarely isolated in the study area).…”
Section: Cliffs Talus Slopes and Island Biogeography Of Bryophytessupporting
confidence: 77%
“…In most of the previous studies, species richness of bryophytes was found to be independent of the degree of isolation of both true islands (Menzel & Passow-Schindhelm, 1990;Dirkse, Bouman & Losada-Lima, 1993;Frahm et al, 1996) and habitat islands (Kimmerer & Driscoll, 2000). The lack of relationship between bryophyte species richness and habitat isolation was confirmed for cliffs in our study (it was not analysed for talus slopes, which are rarely isolated in the study area).…”
Section: Cliffs Talus Slopes and Island Biogeography Of Bryophytessupporting
confidence: 77%
“…In Africa this species is widely distributed mainly in countries south of the equator (Wigginton, 2004(Wigginton, , 2009). It has also been reported from the Cape Verde Archipelago (Frahm et al, 1996).…”
Section: Ochyra and Ochyramentioning
confidence: 64%
“…Förh. 41 Notes: A specimen collected by Norman at the type locality and stored under the name Biatorella coeloplata in TROM is here designated the lectotype. Norman (1884) described a form, Biatorella coeloplata f. carbonata, for older apothecia; we use a single specimen to lectotypify this form as well as the species.…”
Section: Taxonomymentioning
confidence: 99%